Challenging a 15‐year‐old claim: The North Atlantic Oscillation index as a predictor of spring migration phenology of birds. (7th January 2018) - Haest, Birgen; Hüppop, Ommo; Bairlein, Franz
Abstract: Many migrant bird species that breed in the Northern Hemisphere show advancement in spring arrival dates. The North Atlantic Oscillation (NAO) index is one of the climatic variables that have been most often investigated and shown to be correlated with these changes in spring arrival. Although the NAO is often claimed to be a good predictor or even to have a marked effect on interannual changes in spring migration phenology of Northern Hemisphere breeding birds, the results on relations between spring migration phenology and NAO show a large variety, ranging from no, over weak, to a strong association. Several factors, such as geographic location, migration phase, and the NAO index time window, have been suggested to partly explain these observed differences in association. A combination of a literature meta‐analysis, and a meta‐analysis and sliding time window analysis of a dataset of 23 short‐ and long‐distance migrants from the constant‐effort trapping garden at Helgoland, Germany, however, paints a completely different picture. We found a statistically significant overall effect size of the NAO on spring migration phenology (coefficient = −0.14, SE  = 0.054), but this on average only explains 0%–6% of the variance in spring migration phenology across all species. As such, the value and biological meaning of the NAO as a general predictor or explanatory variable for climate change effects on migration phenology of birds, seems highly questionable. We found little to no definite support for previously suggested factors, such as geographic location, migration phenology phase, or the NAO time window, to explain the heterogeneity in correlation differences. We, however, did find compelling evidence that the lack of accounting for trends in both time series has led to strongly inflated (spurious) correlations in many studies (coefficient = −0.13, SE  = 0.019). Abstract : The North Atlantic Oscillation (NAO) has often been claimed to correlate with changes in spring arrival dates in birds. With a literature meta‐analysis, and analyses of a dataset of 23 migratory birds from the trapping garden at Helgoland, we show that the NAO only explains 0%–6% of the variance in spring migration phenology. We found little support for previously suggested factors, such as geographic location, migration phenology phase, or the NAO time window, to explain the heterogeneity in correlations. We did find compelling evidence that the lack of accounting for trends in both time series has led to spurious correlations in many studies.